Internalisasi Nilai-nilai Multikultural dalam Proses Pembelajaran Bahasa Arab di Pendidikan Tinggi - Miftachul Taubah; Faisol Nasar Bin Madi; Sofkhatin Khumaidah; Dustnazar Khimmataliev (Alsina : Journal of Arabic Studies, 2025)
Although Arabic is the sacred language of the Qur’an and the key to understanding Islamic teachings, in Indonesia it is often misunderstood due to its association with socio-political issues. This study is significant in strengthening the values of tolerance, pluralism, and nationalism through an inclusive and humanistic Arabic language learning approach at Yudharta University Pasuruan (UYP), an Islamic boarding school–based university that upholds diversity. The aim of this research is to analyze the concept, implementation, and multicultural values internalized in Arabic language learning. The study employs a qualitative case study approach using interviews, moderate participant observation, and documentation, with data analyzed through condensation, presentation, and verification stages using source and technique triangulation. The findings show that the internalization of multicultural values at UYP is based on three main pillars: institutional policy, curriculum integration, and pesantren culture. Implementation is carried out through active and inclusive learning, value integration in assignments, and experiential field activities. The dominant values include tolerance, togetherness, equality, and cultural openness. This study produces the Multicultural Learning Ecosystem Model, illustrating that the internalization of values occurs simultaneously through structural, pedagogical, cultural, and experiential dimensions, serving as a model for multicultural-oriented Arabic language education.